1998
DOI: 10.1074/jbc.273.18.11100
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational Processing and Turnover Kinetics of Presynaptically Targeted Amyloid Precursor Superfamily Proteins in the Central Nervous System

Abstract: The amyloid precursor superfamily is composed of three highly conserved transmembrane glycoproteins, the amyloid precursor protein (APP) and amyloid precursor-like proteins 1 and 2 (APLP1, APLP2), whose functions are unknown. Proteolytic cleavage of APP yields the ␤A4 peptide, the major component of cerebral amyloid in Alzheimer's disease. Here we show that five post-translationally modified, full-length species of APP and APLP2 (but not APLP1) arrive at the mature presynaptic terminal in the fastest wave of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 52 publications
5
49
1
Order By: Relevance
“…Hematoxyline counterstaining revealed the linearly distributed granules to be intraaxonal, indicating presence and transport of -sAPP in the axon. The normal presence of -sAPP in the axon is supported by several previous studies [22][23][24][25][26] and the axonally transported APP can be processed in the axolemma or the axon [28,29]. Newly synthesised APP is believed to be delivered to the synaptic terminal by fast anterograde axonal transport and then transported to the dendrites by a transcytotic mechanism [23].…”
Section: Discussionsupporting
confidence: 53%
“…Hematoxyline counterstaining revealed the linearly distributed granules to be intraaxonal, indicating presence and transport of -sAPP in the axon. The normal presence of -sAPP in the axon is supported by several previous studies [22][23][24][25][26] and the axonally transported APP can be processed in the axolemma or the axon [28,29]. Newly synthesised APP is believed to be delivered to the synaptic terminal by fast anterograde axonal transport and then transported to the dendrites by a transcytotic mechanism [23].…”
Section: Discussionsupporting
confidence: 53%
“…We have shown that the 2z tag does not alter the proteolytic processing of APP but stabilizes its C-terminal fragments and enhances their detection (23). This method has enabled the detection of a novel ⑀-cleavage site of APP at the C-terminal end of the transmembrane domain, between Leu 49 and Val 50 (23). Thus, the 2z tag was fused to the C termini of APLP-1 and APLP-2-763, and these constructs, which we termed APLP-1-2z and APLP-2-2z, respectively, were overexpressed in SH-SY5Y cells.…”
Section: Detection Of the C-terminal Fragments Of App695 Aplp-1 Andmentioning
confidence: 99%
“…An additional cleavage within the APP ectodomain at position Ϫ12 (relative to A␤), which was termed ␦-cleavage, has only been observed in hippocampal neurons so far (22). Recently, we and others have identified a presenilindependent cleavage at the C-terminal end of the APP transmembrane domain between Leu 49 and Val 50 , which we termed ⑀-cleavage (23)(24)(25)(26), that is homologous to the S3 cleavage of Notch (27,28). The exact mechanism of the two presenilin-dependent ␥-and ⑀-cleavages within the transmembrane domain of APP remains unclear.…”
mentioning
confidence: 99%
“…APP operates in a cell autonomous fashion to mediate axonal pruning in the adult after changes in sensory input, similar to its cell autonomous role in sensory neuron and retinal axon pruning (8,29). Previous work demonstrates that APP is expressed both pre-and postsynaptically (13)(14)(15)(16)(17)(18) and is present in growth cones (30,31). Furthermore, the E1 portion of the APP protein plays a role in cell adhesion (27).…”
Section: Discussionmentioning
confidence: 99%